Innovative Human Resource Practices to Improve Work-Life Balance and Talent Retention: Strategic Review and Implementation - Rinawati Rinawati; Paulus Perey Untajana; Anthoneta Kopong (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
This research investigates the impact of new HR practices to WLB and talent retention in a multinational ICT company in Indonesia. Utilising a quantitative descriptive correlational design, this research examines the contribution of innovative HR policies including work flexibility and welfare to the balance between employees' work-life matters as well as how such balances impact on employees' intention to stay in the organisation. Data collection was done with structured questionnaires, with a total of 370 respondents selected using simple random sampling technique. Based on the Multiple Linear Regression Analysis shows that Innovative HR practices has a positive significant both directional influence work-life balance which is signified by regression coefficients (B) = 0.62 and R²=0.38 (Table 3). Additionally, the joint effect of innovative HR practices and work-life balance on talent retention is also meaningful with regression coefficients of 0.40 at innovation HR practices side and 0.45 at work life balance side (R²=0.47). The conclusion that can be drawn from these findings is that organisations which implement innovative HR policies attract a more loyal employee base, reduce staff turnover and can also nurture a positive impact towards the public image of an organisation (Steur et al., 2012). The article also provides theoretical contributions and practical implications for HR management to design polices that address work-life balance so as to facilitate talent retention thereby leading to enhance organizational sustainability and productivity.